Functional mimicry revealed by the crystal structure of an eIF4A:RNA complex bound to the interfacial inhibitor, desmethyl pateamine A. Issue 6 (17th June 2021) - Naineni, Sai Kiran; Liang, Jason; Hull, Kenneth; Cencic, Regina; Zhu, Mingzhao; Northcote, Peter; Teesdale-Spittle, Paul; Romo, Daniel; Nagar, Bhushan; Pelletier, Jerry
Summary: Interfacial inhibitors exert their biological effects through co-association with two macromolecules. The pateamine A (PatA) class of molecules function by stabilizing eukaryotic initiation factor (eIF) 4A RNA helicase onto RNA, resulting in translation initiation inhibition. Here, we present the crystal structure of an eIF4A1:RNA complex bound to an analog of the marine sponge-derived natural product PatA, C5-desmethyl PatA (DMPatA). One end of this small molecule wedges itself between two RNA bases while the other end is cradled by several protein residues. Strikingly, DMPatA interacts with the eIF4A1:RNA complex in an almost identical fashion as rocaglamide A (RocA), despite being completely unrelated from a structural standpoint. The structural data rationalize the ability of PatA analogs to target a wider range of RNA substrates compared to RocA. We define the molecular basis of how DMPatA is able to clamp eIF4A1 onto RNA, imparting potent inhibitory properties to this molecule. Graphical abstract: Highlights: Crystal structure of eIF4A1⋅AMPPNP⋅poly (AG)5 ⋅C5-desmethyl PatA (DMPatA). DMPatA acts an interfacial inhibitor, interacting with both eIF4A1 and RNA. DMPatA clamps eIF4A1 onto both polypurine and polypyrimide RNA templates. DMPatA and rocaglamide A (RocA) binding sites on eIF4A1 are largely overlapping. Abstract : Naineni, Liang et al. solved the crystal structure of an eIF4A1⋅AMPPNP⋅r(AG)5 ⋅DMPatA complex. DMPatA stabilizes eIF4A1/RNA complexes to inhibit translation initiation. The structure rationalizes the broad RNA targeting range of DMPatA, defines the molecular interactions with eIF4A1, and provides a template for future analog design.